Targeted thorium-227 conjugates as treatment options in oncology - Karlsson, Jenny; Schatz, Christoph A.; Wengner, Antje M.; Hammer, Stefanie; Scholz, Arne; Cuthbertson, Alan; Wagner, Volker; Hennekes, Hartwig; Jardine, Vicki; Hagemann, Urs B. (Frontiers in Medicine, 2023)
Targeted alpha therapy (TAT) is a promising approach for addressing unmet needs in oncology. Inherent properties make α-emitting radionuclides well suited to cancer therapy, including high linear energy transfer, penetration range of 2–10 cell layers, induction of complex double-stranded DNA breaks, and immune-stimulatory effects. Several alpha radionuclides, including radium-223 (223Ra), actinium-225 (225Ac) and thorium-227 (227Th), have been investigated. Conjugation of tumor targeting modalities, such as antibodies and small molecules, with a chelator moiety and subsequent radiolabeling with α-emitters enables specific delivery of cytotoxic payloads to different tumor types. 223Ra dichloride, approved for the treatment of patients with metastatic castration-resistant prostate cancer with bone-metastatic disease and no visceral metastasis, is the only approved and commercialized alpha therapy. However, 223Ra dichloride cannot currently be complexed to targeting moieties. In contrast to 223Ra, 227Th may be readily chelated, which allows radiolabeling of tumor targeting moieties to produce targeted thorium conjugates (TTCs), facilitating delivery to a broad range of tumors. TTCs have shown promise in preclinical studies across a range of tumor-cell expressing antigens. A clinical study in hematological malignancy targeting CD22 has demonstrated early signs of activity. Furthermore, preclinical studies show additive or synergistic effects when TTCs are combined with established anti-cancer therapies, for example androgen receptor inhibitors, DNA damage response inhibitors such as poly(ADP)-ribose polymerase inhibitors or ataxia telangiectasia and Rad3-related kinase inhibitors, as well as immune checkpoint inhibitors.